The Role of Village-Owned Enterprises (BUMDES) for The Village Community Economy - Irim Tiara Puri; Khoirunurrofik Khoirunurrofik (Economics Development Analysis Journal, 2021)
Regional disparities between rural and urban areas in Indonesia are still being an important issue inthe economic development. The government has carried out an economic stimulus in the village,one of them is through the Village Fund program for village development. One of the potentialpositive effects of implementing the Village Fund in Indonesia is creating a local economicinstitution that is expected to be able to develop the competition between villages through Village-Owned Enterprises (BUMDes). This study aimed to find out the empirical evidence whetherBUMDes, as one of the programs driving the village economy affected the welfare of ruralcommunities by looking at the differences in the improvement of the village economy. This studyused BUMDes and Village Potential (Podes) data in 2014 and 2018, and Village Fund Allocationas a proxy for economic activity at the village level by using the econometric model approach ofPropensity Score Matching and Difference in Difference with a fixed effect model. The resultsshowed that villages that had BUMDes gave a greater effect than the ones which did not haveBUMDes in improving the economy of the village community.